Additive manufacturing of bioactive glasses and silicate bioceramics - Gmeiner, R.; Deisinger, Ulrike; Schönherr, J.; Lechner, B.; Detsch, Rainer; Boccaccini, Aldo R.; Stampfl, J. (Journal of Ceramic Science and Technology, 2015)
This paper reviews the application of a broad range of additive manufacturing technologies (AMTs), including Stereolithographic Ceramic Manufacturing (SLCM/LCM), 3D-Printing, indirect and direct Selective Laser Sintering/Melting (SLS/SLM), Dispense Plotting and Inkjet Plotting on bioactive glasses (BGs) and silicate bioceramics to fabricate a variety of dense and porous structures for biomedical applications (e.g. bone replacement materials). Topical studies in the literature are complemented by recent data of the authors' own work, highlighting the state of the art of additive bioceramic production. The specific characteristics of the technologies used, their advantages and disadvantages and the scope for future research in this field are discussed. To date, many studies focus on 45S5 Bioglass® due to its broad commercial availability. However, other bioactive glass formulations and sol-gel derived BGs are being also considered in the context of AMTs. As the geometrical accuracy and mechanical properties of the fabricated parts strongly vary among the different AMTs, in-depth knowledge of the detailed capabilities of each production process targeted for BGs and other silicate bioceramic materials, as collated in this review, provides information on the basic requirements and challenges for establishing follow-up studies and for possible expansion of the application fields of such additive-manufactured structures.
Keywords: Additive manufacturing; Bioactive glasses; Scaffolds; Silicate bioceramics

Electromagnetic analysis of conductor track surface roughnesses from 1 GHz to 110 GHz - Talai, Armin; Gmeiner, Björn; Wegener, Carsten Moritz; Roosen, Andreas; Kölpin, Alexander; Steinhäußer, Frank; Deisinger, Ulrike; Bittner, Achim; Schmid, Ulrich; Weigel, Robert (Electromagnetics in Advanced Applications (ICEAA), 2014 International Conference on, 2014)
Conductor tracks comprise a frequency dependent attenuation of electromagnetic waves, since with increasing frequency the current flow is displaced to the near surface region due to the skin effect. Therefore, the effective length of the conductor is increased by the surface roughness, while its effective cross-section is decreased by current displacement, both leading to higher metallization loss. In this paper, surface topographies of typical conductor materials were recorded by confocal microscopy and rebuilt as 3D CAD models. Subsequent electromagnetic simulations reveal the influence due to roughness on high frequency characteristics for physical vapor deposited, thick film and photochemically etched microstrips.
UnivIS-Import:2015-04-17:Pub.2014.tech.IMMD.lsinfs.electr